Gender Differences in Behçet’s Disease Associated Uveitis - Didar Ucar-Comlekoglu; Austin Fox; H. Nida Sen (Journal of Ophthalmology)
Behçet’s disease is a systemic vasculitis of unknown etiology, characterized by oral and genital ulceration, skin lesions, and uveitis as well as vascular, central nervous system, and gastrointestinal system involvement. It is prevalent in the Middle East, Mediterranean, and Eastern Asia. The aim of this review is to evaluate the gender differences in clinical manifestations of Behçet’s disease, treatment responses, mortality, and morbidity. Behçet’s disease has been reported to be more prevalent in males from certain geographic regions and particular ethnic groups; however, recent reports indicate more even gender distribution across the world. There are gender differences in clinical manifestations and severity of the disease. Ocular manifestations, vascular involvement, and neurologic symptoms are more frequently reported in male patients whereas oral and genital ulcers, skin lesions, and arthritis occur more frequently in female patients. The disease can have a more severe course in males, and overall mortality rate is significantly higher among young male patients.